FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Pebi Putra Tri Prabowo; Marsono Marsono (Diponegoro Journal of Accounting, 2013)
One of the qualitative characteristics in the delivery of the financial statements is relevant, the realization can be seen from reporting timeleness. Timeleness can be seen from the audit delay, that mean the time between the closing date until the date of auditor reporting. This study was a replication of a previous study conducted by Subekti and Wulandari (2004). The difference from the previous study was the addition of several variables and the addition of a three-year study period (2009-2011). This study aimed to analyze the effect of firm size, profitability, solvency, corporate income, the size of the auditor, the auditor's opinion, and the existence of the audit committee during audit delay in manufacturing companies that listing at Indonesia Stock Market. This study focused on manufacturing companies. The data used are secondary data, the financial statements of 72 companies listed on the Indonesia Stock Exchange in the year 2009-2011. To prove the hypothesis using regression test that begins with previous classic assumption test. Simultaneous testing concluded that all independent variables simultaneously affect dependent variable. Partial testing of the outcome find  from seven factors,only  six factors influence the audit delay, these are  company size, profitability, solvency, size of the auditor, the auditor's opinion, and the existence of the audit committee . Then company's income statement has no effect on audit delay. The results of this study can help the public accountant profession in an effort to improve the efficiency and effectiveness of the audit process by controlling the factors that could cause the audit delay